Oligoarray comparative genomic hybridization of renal cell tumors that developed in patients with acquired cystic renal disease - Kuntz, Eva; Yusenko, Maria; Nagy, Anetta; Kovacs, Gyula (Human pathology, 2010)
Renal cell carcinoma occurs at higher frequency in acquired cystic renal disease than in the general population. We have analyzed 4 tumors obtained from the kidneys of 2 patients with acquired cystic renal disease, including 2 conventional renal cell carcinomas and 2 acquired cystic renal disease-associated tumors, for genetic alterations. DNA changes were established by applying the 44K Agilent Oligonucleotide Array-Based CGH (Agilent Technologies, Waldbronn, Germany), and mutation of VHL gene was detected by direct sequencing of the tumor genome. DNA losses and mutation of the VHL gene, which are characteristic for conventional renal cell carcinomas, were seen in 2 of the tumors. The acquired cystic renal disease-associated eosinophilic-vacuolated cell tumor showed gain of chromosomes 3 and 16. No DNA alterations occurred in the papillary clear cell tumor. We suggest that not only the morphology but also the genetics of renal cell tumors associated with acquired cystic renal disease may differ from those occurring in the general population.